Where are the Animals in Sustainable Development? Religion and the Case for Ethical Stewardship in Animal Husbandry. (May 2016) - Narayanan, Yamini
Abstract: The rights of livestock that are designated as food/farm animals have been a blindspot across development discourse and policies in spite of compelling moral (and socio‐ecological) factors. They are regarded as 'resources' to sustain growth, leading to food production systems that support factory farming and invasive animal husbandry practices. The paper argues that religion and sustainable development are unlikely partners in the commodification of animals in these policies. Capitalist‐driven interpretations of religion support the objectification of animals. Sustainable development, an efficiency‐driven growth paradigm, is concerned with the preservation of finite natural resources. Sentient factory farmed animals are seen as infinite resources .Using Christianity and Hinduism as examples, the paper argues that religion can also shape alternative animal husbandry/food production practices, and expand the social justice element of sustainable development to encompass what I term 'sociozoological justice' in economic systems that heavily involve animals. Copyright © 2016 John Wiley & Sons, Ltd and ERP Environment.